Serial biomarker measurements may be helpful to predict the successful application of high flow nasal cannula in COVID-19 pneumonia patients - Reid Ikeda; Andrew Pham; Guangxiang Zhang; Jennifer F. Lai; James Davis; Gehan Devendra (Scientific Reports)
Abstract High flow nasal cannula (HFNC) can reduce the need for intubation in patients with coronavirus disease-19 (COVID-19) pneumonia induced acute hypoxemic respiratory failure (AHRF), but predictors of HFNC success could be characterized better. C-reactive protein (CRP) and D-dimer are associated with COVID-19 severity and progression. However, no one has evaluated the use of serial CRP and D-dimer ratios to predict HFNC success. We retrospectively studied 194 HFNC-treated patients admitted between August 2020 and October 2022. CRP and D-dimer levels relative to baseline at HFNC initiation were calculated up to three days thereafter. Intubated and non-intubated patient comparisons were assessed by the Kruskal-Wallis rank sum test and t-test. Ninety-two patients were intubated and 102 were not. Median CRP ratios were lower in non-intubated versus intubated patients (0.69 v. 0.96, p = 0.050 for Day 1; 0.49 v. 0.61, p = 0.028 for Day 2; 0.33 v. 0.64, p = 0.008 for Day 3). D-dimer ratios did not change. CRP ratio monitoring in patients with AHRF due to COVID-19 within the first three days of HFNC application can serve as an objective adjunctive clinical tool to identify individuals who can continue to be supported with HFNC without escalating to invasive mechanical ventilation.